Perception of Higher Secondary School Teachers on the Impact of Anthropogenic Global Warming on Environment - P., Aneeshya (JOURNAL OF INDIAN EDUCATION, 2018)
Global warming, the term used to describe a gradual increase in the average temperature of the earth’s atmosphere and its oceans, a change that is believed to be permanently changing the earth’s climate forever. Anthropogenic global warming refers to the increase in the average temperature of the climate system in recent decades because of human induced actions. Anthropogenic global warming is a worldwide environmental problem not only affecting the nature, but it also affects the life and homes of millions of people. Anthropogenic global warming can be minimised to a great extent, if we eliminate the causes which are mostly human made. The responsibility of controlling anthropogenic global warming rests both on the individual as well as the state. The present investigation was conducted to study the perception of higher secondary school teachers on the impact of anthropogenic global warming on environment. Normative survey was conducted among 390 higher secondary school teachers of various schools of Kannur, Thrissur and Trivandrum districts. The tool used for the study was Teacher’s Perception Scale on the Impact of Anthropogenic Global Warming (TPSIAGW). The findings of the study reveal that higher secondary school teachers have an average perception regarding the impact of anthropogenic global warming on environment.